Upaya Pembinaan Membaca Al-Qur’an pada Santri di DTA Al-Hasanah Margasari Karawang - Muhammad Arrfatkhur Rizky; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This research departs from the background of reading the Koran in schools at the Diniyyah Takmiliah Awaliyah Institute, which focuses on reading verses of the Koran tartil and fluently and being able to understand it and learn it to apply it to everyday life day with even better Al-Qur'an recitation, the purpose of the researcher is to describe the learning that is applied at the Al-Hasanah DTA school in providing learning to students and applying appropriate methods to facilitate Al-Qur'an recitation for students at school . The method used in this study is a qualitative method which is taken based on data in the field by way of observation studies, interviews, and documentation so that research results can be found and conclusions drawn. The results obtained from the research are the efforts of DTA teachers to improve the quality of students' reading of the Qur'an by carrying out several supporting factors that can be understood by students regarding how to read the Al-Qur'an properly and correctly, which starts at the beginning of learning and after learn by using Yanbu'a method.